Pentecostal Megachurches in Southeast Asia : Negotiating Class, Consumption and the Nation - Chong, Terence (Book collections on Project MUSE., 2018)
Charismatic pastors, fast-paced worship sessions, inspirational but shallow theology, and large congregations -- these are just some of the associated traits of Pentecostal megachurches. But what lies beneath the veneer of glitz? What are their congregations like? How did they grow so quickly? How have they managed to negotiate local and transnational challenges? This book seeks to understand the growth and popularity of independent Pentecostal megachurches in Southeast Asia. Using an ethnographic approach, the chapters examine Pentecostal megachurches in Malaysia, Indonesia, the Philippines, and Singapore. Each chapter dwells on the development of the megachurch set against the specific background of the country's politics and history.